2023
DOI: 10.1186/s12951-023-01942-y
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomal miR-27b-3p alleviates liver fibrosis via downregulating YAP/LOXL2 pathway

Abstract: Lysyl oxidase-like 2 (LOXL2) is an extracellular copper-dependent enzyme that plays a central role in fibrosis by catalyzing the crosslinking and deposition of collagen. Therapeutic LOXL2 inhibition has been shown to suppress liver fibrosis progression and promote its reversal. This study investigates the efficacy and underlying mechanisms of human umbilical cord-derived exosomes (MSC-ex) in LOXL2 inhibition of liver fibrosis. MSC-ex, nonselective LOX inhibitor β-aminopropionitrile (BAPN), or PBS were administ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These exosomes have been found to inhibit TGF-1/SMAD signaling to inhibit LF and stimulate hepatocyte proliferation, leading to a protective effect on hepatocytes. 85 , 88 Similar anti-LF and hepatoprotective and regenerative effects were also observed with exosomes from various sources of MSCs, including bmMSCs, 89 , 90 hucMSCs, 91 , 92 hlMSCs, 93 induced pluripotent MSCs, 94 heMSCs, 95 blood-derived MSCs, 96 and adipose-derived MSCs of adipose origin. 97 Numerous studies have linked the anti-LF impact of macrophages to the exosomes derived from MSCs.…”
Section: Exosomes Targeting Macrophages and Their Roles In Lfmentioning
confidence: 62%
“…These exosomes have been found to inhibit TGF-1/SMAD signaling to inhibit LF and stimulate hepatocyte proliferation, leading to a protective effect on hepatocytes. 85 , 88 Similar anti-LF and hepatoprotective and regenerative effects were also observed with exosomes from various sources of MSCs, including bmMSCs, 89 , 90 hucMSCs, 91 , 92 hlMSCs, 93 induced pluripotent MSCs, 94 heMSCs, 95 blood-derived MSCs, 96 and adipose-derived MSCs of adipose origin. 97 Numerous studies have linked the anti-LF impact of macrophages to the exosomes derived from MSCs.…”
Section: Exosomes Targeting Macrophages and Their Roles In Lfmentioning
confidence: 62%
“…Over the past several years, the clinical studies of RIF therapies have concentrated on antifibrotic, including anti-fibrosis antibodies and YAP inhibitors 24 , 25 . Unfortunately, these treatment strategies have not achieved good results and were not significantly reduce fibrosis in clinical tests.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway is highly conserved during evolution. A large amount of evidence has shown that the Hippo pathway plays an important regulatory role in the process of fibrosis of the liver and kidney, which are derived from mesoderm as the same as the uterus [ 45 , 46 ] and an in vitro study had shown that MenSCs could activate the Hippo pathway in EndoSCs through paracrine to inhibit the activation of fibroblasts and reduce TGF-β1-induced EndoSCs fibrosis [ 25 ]. Our previous results also found that MenSCs-EXO treatment decreased the expression level of YAP in the endometrium of IUA.…”
Section: Discussionmentioning
confidence: 99%